Serum neurofilament light chain is increased in hereditary spastic paraplegias - Wilke, Carlo (Ann Clin Transl Neurol, 2018)
Blood biomarkers are still largely missing in hereditary spastic paraplegias (HSPs). We here explored Neurofilament light chain (NfL) as a biomarker in HSP. Serum NfL was assessed in 96 HSP (63 genetically confirmed), 96 healthy control, and 33 ALS subjects by single molecule array (Simoa). Compared to controls, NfL was increased in HSP (P < 0.001), correlating with cross‐sectional disease progression (ρ = 0.28). Levels were lower than in ALS (P < 0.001), allowing to differentiate HSP from ALS (AUC = 0.91). Serum NfL might serve as a biomarker in HSP indicating neuronal damage and, if confirmed longitudinally, disease progression. It might also support differentiating HSP from ALS.